Narrating Motherhood as Experience and Institution: Experimental Life-Writing in Mary Kelly’s Post-Partum Document (1973–79) - Wierzchowska, Justyna (Studia Anglica Posnaniensia, 2016)
This article explores American visual artist Mary Kelly’s autobiographical work Post-partum document in reference to the politics of life writing. Resorting to Lacanian psychoanalysis, a pastiche of scientific narratives and other (auto-)narrative strategies, in her work Kelly documented the first five years of her son’s life from his weaning from the breast until the day when he wrote his name. By documenting her child’s development, the artist also recorded the process of her own formation as a maternal subject, a formation gradually worked out through an evolving relationship with her son. In her work, the artist made vivid the incompatibility and limitations of various narrative frameworks in retelling a fundamentally relational experience that verges on the mental and bodily, and which is necessarily mediated by the patriarchal ideology. This article analyses Kelly’s conflicting narrative strategies that fail to successfully represent the mother-child formative relationship and which demonstrate the mother’s ideological alienation. It reads Kelly’s work politically, exploring the ways in which Post-partum document’s (auto-)narrative voices address questions and dilemmas of the feminine/maternal subject, the subject’s formation, and the limits of its (self-) representation within patriarchy. The article argues that Kelly challenges the traditional autobiographic genre by attending to her lived experience as a mother and the culturally repressed maternal desire.